1990
DOI: 10.1364/ao.29.002392
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence imaging inside an internal combustion engine using tunable excimer lasers

Abstract: Tunable excimer lasers are used to obtain 2-D images of molecular (and some state-specific) density distributions inside a cylinder of a modified four-cylinder in-line engine that has optical access. Natural fluorescence (i.e., without a laser) is used for some OH pictures, normal laser-induced fluorescence (LIF) for those of NO and of the isooctane fuel, and laser-induced predissociative fluorescence (LIPF) for other OH pictures and for those of O(2). Relevant spectroscopy is done to find the laser and fluore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

1992
1992
2009
2009

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 169 publications
(22 citation statements)
references
References 12 publications
0
22
0
Order By: Relevance
“…Studies in the near ultraviolet ͑400-10 nm͒ and near infrared ͑700-1215 nm͒ are becoming more common as near-infrared lasers and frequency-doubling methods improve. LIF has been applied extensively to combustion measurements in flames 168 and the density in an engine cylinder at different locations was measured by Andresen et al 169 …”
Section: H Laser-induced Fluorescencementioning
confidence: 99%
“…Studies in the near ultraviolet ͑400-10 nm͒ and near infrared ͑700-1215 nm͒ are becoming more common as near-infrared lasers and frequency-doubling methods improve. LIF has been applied extensively to combustion measurements in flames 168 and the density in an engine cylinder at different locations was measured by Andresen et al 169 …”
Section: H Laser-induced Fluorescencementioning
confidence: 99%
“…The dissociation is so fast that the collisional quenching rate is negligible compared with the predissociation rate. Andresen and coworkers [6,7] first applied the LIPF technique to observe OH species in Bunsen flames and internal combustion engine using a KrF excimer laser. They concluded that the use of LIPF could greatly reduce the quenching problem and allow quantitative measurements of OH concentrations at elevated pressures.…”
Section: Introductionmentioning
confidence: 99%
“…PLIF has been well established in industrial systems [4][5][6][7][8] . Mie scattering is used to visualize the liquid fuel and may be combined with fuel PLIF in a variety of ways to image drop size 3 or describe the extent of vaporization 9 .…”
Section: Introductionmentioning
confidence: 99%